Death penalty cases : - Latzer, Barry (Butterworth Heinemann, 2001)
This brand new edition of Death Penalty Cases makes the most manageable comprehensive resource on the death penalty even better. It includes the most recent cases, including Kennedy v. Louisiana, prohibiting the death penalty for child rapists, and Baze v. Rees, upholding execution by lethal injection. In addition, all of the cases are now topically organized into five sections: * The Foundational Cases. The Death Penalty Trial * Post-conviction Review * Execution Issues The introductory essays on the history, administration, and controversies surrounding capital punishment have been thoroughly revised. The statistical appendix has been brought up-to-date, and the statutory appendix has been restructured. For clarity, accuracy, complete impartiality and comprehensiveness, there simply is no better resource on capital punishment available.